2006
DOI: 10.1590/s1807-59322006000200009
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Progression of Bone Plasmacytomas to Multiple Myeloma

Abstract: PURPOSE: To evaluate the clinical aspects, diagnoses, prognostic factors, and percent progression of plasmacytoma to multiple myeloma. MATERIALS AND METHODS: 103 medical records of patients suspected of plasmacytoma were surveyed covering the period between 1950 and 1998, and 30 were selected for analysis. Patients were classified into 2 groups: patients who did (n = 17) and did not (n = 13) progress to multiple myeloma. Comparative statistics regarding a variety of clincial aspects were developed. RESULTS: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
8
0
3
Order By: Relevance
“…However, Bertanha et al, found that patients who progressed to MM were younger than those who did not. In their study, the average time of progression to MM was 41 months [9]. However, the evidence of the risk factor analysis was low because the small sample size of the two groups was only compared using the t test analysis.…”
Section: Discussionmentioning
confidence: 96%
“…However, Bertanha et al, found that patients who progressed to MM were younger than those who did not. In their study, the average time of progression to MM was 41 months [9]. However, the evidence of the risk factor analysis was low because the small sample size of the two groups was only compared using the t test analysis.…”
Section: Discussionmentioning
confidence: 96%
“…3 The solitary bone plasmacytoma represents a 10-year survival rate up to 85% patients 6 ; however, 50% can progress to a MM variant, with worse prognosis. 7 The diagnosis work-up should include a complete anamnesis, physical examination, laboratory studies, tumor histopathology confirmation, protein electrophoresis, and evaluation for the presence of Bence Jones protein (Ig light chains in urine). 5 In solitary bone plasmacytoma, the symptoms depend on the localization of the lesion and could be from lumbar pain with radicular signs to sphincter compromise.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, numerosos equipos prefieren la radioterapia como primera opción, incluso en los casos en que la resección ha sido efectuada por falta de diagnóstico, refiriendo buena respuesta en más del 90% de los casos [11][12][13][14] .…”
Section: Discussionunclassified
“…La quimioterapia parece no brindar claros beneficios en supervivencia ni en prevención de la progresión a Mieloma Múltiple 3,12,14 . Esta progresión, ocurre más frecuentemente dentro de los cuatro primeros años, con un promedio de 41 meses.…”
Section: Discussionunclassified